Does Perceived Ease of Usefulness and Perceived Usefulness Effect Customer Attitude and Satisfaction in Social Commerce - Margaretha Pink Berlianto; Fanny Mutiara Dewi; Helen Novi Yanto; William M. Tan; Aulia Hidayati (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
As social media commerce has become extremely popular and an integral part of the world economy in recent years, identifying the factors influencing consumer attitudes towards social media sites has become a significant goal of many researchers in academia and industry. This study aims to identify factors that predict consumer attitudes and satisfaction towards using Instagram. This study uses 190 respondents who are in Jabodetabek using convenience sampling. The results showed that Perceived usefulness has a positive effect on attitude and satisfaction, Perceived ease of use has a positive effect on satisfaction, and customer attitude has a positive effect on satisfaction. This research successfully contributes that social commerce business actors need to pay attention to the perceived usefulness and perceived of use of the social commerce they manage and need to improve customer attitudes towards their social commerce.